Diffusion-Weighted MR Imaging of an Acute Venous Stroke: Case Report - Peeters, Els; Stadnik, Tadeusz; Bissay, Frédéric; Schmedding, Eric; Osteaux, Michel (American Journal of Neuroradiology, 2001)
Summary: A patient with a superior sagittal sinus thrombosis had progressively worsening symptoms and signs that resolved after IV heparin therapy. MR imaging revealed abnormalities in diffusion, similar to those seen with acute arterial stroke. Abnormalities shown on a T2-weighted fast spin-echo and fluid-attenuated inversion recovery images resolved completely. The findings in this report contradict those from previous reports that suggest diffusion-weighted imaging with quantitative apparent diffusion coefficients may be used in selecting patients for dural venous sinus thrombolysis.